Staying Connected While Staying Distant: Social Media Engagement of Food Banks in Texas in the Wake of the COVID-19 Pandemic - Hoang, Thanh Thi (Human Service Organizations: Management, Leadership & Governance, 2023)
This study explores the social media engagement of human service nonprofits during the early phase of the COVID-19 pandemic. We analyzed 2,726 tweets from 15 food banks in Texas to understand their communication and audience engagement on social media. During the early outbreak, food banks were more active on social media, and these organizations primarily shared community-building and informational content. Before the pandemic, community-building content led to the highest engagement level. However, action and informational content saw greater engagement during the crisis. Our findings reveal that online audiences perceive the importance of each content type differently in varying circumstances. By understanding preferences and needs of online audiences, human service nonprofits can harness the power of social media to amplify their impact while operating during times of crisis.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/23303131.2023.2237090
Keywords: Audience engagement; crisis; dept.psc; food banks; peer-reviewed; social media

Where are we when the community looks for us? A social network analysis of the self-organized network #TwitterFoodBank - Hoang, Thanh Thi (Communication and the Public, 2023)
Traditional crisis management approaches have often overlooked the role of community and nonprofit organizations. In this study, we investigated how nonprofits and communities contributed to problem-solving during crises through self-organization on social media. We applied social network analysis to 17,732 interactions using #TwitterFoodBank, a self-organized network emerged during the early stage of COVID-19 to address food insecurity. Our results highlighted the significant role of nonprofits in coordinating the community’s self-organized network. However, they also revealed a lack of coordination among these organizations in maintaining a viable network. These findings have valuable implications for nonprofits seeking to leverage the potential of online self-organized communities in crisis management.
Keywords: dept.psc; peer-reviewed

Exploring Perceived Fairness in Performance Evaluation Among Telecommuting Employees in Public Agencies - Aggarwal, Jyoti; Hoang, Thanh (Public Administration Quarterly, 2025)
Keywords: Business; Economics; Engineering; Marketing; Political science; Psychology; Public relations; Public sector; Telecommuting; Work (physics); dept.psc; fairness; federal government; organizational justice; performance evaluation; public sector; telecommute